Associations of key diet-quality indexes with mortality in the Multiethnic Cohort: The dietary patterns methods project - Harmon, B.; Boushey, Carol; Shvetsov, Y.; Ettienne, R.; Reedy, J.; Wilkens, L.; Le Marchand, L.; Henderson, B.; Kolonel, L. (American Society for Nutrition, 2015)
Background: Healthy dietary patterns have been linked positively with health and longevity. However, prospective studies in diverse populations in the United States addressing dietary patterns and mortality are limited. Objective: We assessed the ability of the following 4 diet-quality indexes [the Healthy Eating Index-2010 (HEI-2010), the Alternative HEI-2010 (AHEI-2010), the alternate Mediterranean diet score (aMED), and the Dietary Approaches to Stop Hypertension (DASH)] to predict the reduction in risk of mortality from all causes, cardiovascular disease (CVD), and cancer. Design: White, African American, Native Hawaiian, Japanese American, and Latino adults (n = 215,782) from the Multiethnic Cohort completed a quantitative food-frequency questionnaire. Scores for each dietary index were computed and divided into quintiles for men and women. Mortality was documented over 13-18 y of follow-up. HRs and 95% CIs were computed by using adjusted Cox models. Results: High HEI-2010, AHEI-2010, aMED, and DASH scores were all inversely associated with risk of mortality from all causes, CVD, and cancer in both men and women (P-trend < 0.0001 for all models). For men, the HEI-2010 was consistently associated with a reduction in risk of mortality for all causes (HR: 0.75; 95% CI: 0.71, 0.79), CVD (HR: 0.74; 95% CI: 0.69, 0.81), and cancer (HR: 0.76; 95% CI: 0.70, 0.83) when lowest and highest quintiles were compared. In women, the AHEI and aMED showed large reductions for all-cause mortality (HR: 0.78; 95% CI: 0.74, 0.82), the AHEI showed large reductions for CVD (HR: 0.76; 95% CI: 0.69, 0.83), and the aMED showed large reductions for cancer (HR: 0.84; 95% CI: 0.76, 0. 92). Conclusion: These results, in a US multiethnic population, suggest that consuming a dietary pattern that achieves a high diet-quality index score is associated with lower risk of mortality from all causes, CVD, and cancer in adult men and women.